Investigating the Relationship between Software Team Leadership Styles and Turnover Intention - Araújo, Narallynne; Massoni, Tiago; Sarmento, Camila; Santos, Francielle; Oliveira, Ruan (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2022)
In other fields than Software Engineering, previous studies observed that leadership styles could influence employee turnover. This turnover is prominent, especially among software developers, who have identified personal and work issues related to this career decision. This paper is an initial and exploratpry study that investigates the relationship between turnover intention and leadership styles in software teams. These leadership styles were analyzed according to the Full Range Leadership Model (FRLM) using the 6S version of the Multifactor Leadership Questionnaire. We applied it to Brazilian developers, in which we obtained 104 responses. Initial results indicate that developers perceive no significant difference between transformational, transactional, and passive/avoidant leaders, suggesting that these leaders may exhibit mixed styles and characteristics. No leadership style index is significantly correlated with turnover intention, suggesting that these indices are less critical to turnover than other variables previously studied in the literature. Furthermore, the results show that transformational and transactional styles are positively correlated, indicating that these styles can develop together, promoting motivation, guidance, and contributing leaders for self-managed teams, where they can use the passive/avoidant leadership style to determine effective leadership in agile teams. These results were the starting points for our current investigation into leadership in software teams, which aims to observe how effective leadership occurs within teams and how non-leaders perceive this leadership, helping management understand leadership characteristics and how they potentially interfere with development activities.